Islamization of Family and Society: Study of Bangladesh Jama‘at-e-Islami (BJI) - Muhammad Hedayatul, Islam; Fadzli, Adam (2019)
From its establishment in 1941 in the Indian Subcontinent, the Jamaat-e-Islami (JI), a contemporary leading Islamic movement in Bangladesh, represents a comprehensive example of a Muslim group in trying to address the prevailing socio-cultural and politico-economic problems which Muslim nations face. The purpose of this study to examine Bangladesh Jamaate-Islami (BJI) and it’s policy, ideology, social activities and most importantly intellectual activities and involvements in the policies of Islamization of family and society. In this regard, Jamaat’s constitution, literatures and various lectures of the top leaders available were critically analyzed. This study found that the concept of “Islamization of family and society” is used as an important means for an Islamist movement to revert the ultra-secular polity as well as liberal and extreme views not in favor of Islam. This study concludes that based on the true Islamic teachings, the BJI has the potential in promoting a project of Islamization Movement in order to develop and institutionalize a value-oriented family and society based on the worldview of Islam.